Uniting biobank resources reveals novel genetic pathways modulating susceptibility for atopic dermatitis - Sliz Eeva; Huilaja Laura; Pasanen Anu; Laisk Triin; Reimann Ene; Mägi Reedik; FinnGen; Estonian Biobank Research Team; Hannula-Jouppi Katariina; Peltonen Sirkku; Salmi Teea; Koulu Leena; et al. (Elsevier Inc., 2022)
Background: Atopic dermatitis (AD) is a common chronic inflammatory skin disease with high heritability. Previous genome-wide association studies have identified several loci predisposing to AD. These findings explain approximately 30% of the variance in AD susceptibility, suggesting that further work is required to fully understand the genetic underpinnings.
Objective: We sought to gain additional understanding of the genetic contribution to AD risk by using biobank resources.
Methods: We completed a genome-wide meta-analysis of AD in 796,661 individuals (Ncases = 22,474) from the FinnGen study, the Estonian Biobank, and the UK Biobank. We further performed downstream in silico analyses to characterize the risk variants at the novel loci.
Results: We report 30 loci associating with AD (P < 5 × 10-8), 5 of which are novel. In 2 of the novel loci, we identified missense mutations with deleterious predictions in desmocollin 1 and serpin family B member 7, genes encoding proteins crucial to epidermal strength and integrity.
Conclusions: These findings elucidate novel genetic pathways involved in AD pathophysiology. The likely involvement of desmocollin 1 and serpin family B member 7 in AD pathogenesis may offer opportunities for the development of novel treatment strategies for AD in the future.
Keywords: Atopic dermatitis; DSC1; FinnGen; SERPINB7; genome-wide association.
Copyright © 2021 The Authors. Published by Elsevier Inc. All rights reserved.